-8(2b+3)+(17b-3)=0

Simple and best practice solution for -8(2b+3)+(17b-3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(2b+3)+(17b-3)=0 equation:


Simplifying
-8(2b + 3) + (17b + -3) = 0

Reorder the terms:
-8(3 + 2b) + (17b + -3) = 0
(3 * -8 + 2b * -8) + (17b + -3) = 0
(-24 + -16b) + (17b + -3) = 0

Reorder the terms:
-24 + -16b + (-3 + 17b) = 0

Remove parenthesis around (-3 + 17b)
-24 + -16b + -3 + 17b = 0

Reorder the terms:
-24 + -3 + -16b + 17b = 0

Combine like terms: -24 + -3 = -27
-27 + -16b + 17b = 0

Combine like terms: -16b + 17b = 1b
-27 + 1b = 0

Solving
-27 + 1b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '27' to each side of the equation.
-27 + 27 + 1b = 0 + 27

Combine like terms: -27 + 27 = 0
0 + 1b = 0 + 27
1b = 0 + 27

Combine like terms: 0 + 27 = 27
1b = 27

Divide each side by '1'.
b = 27

Simplifying
b = 27

See similar equations:

| -y+2=16-8y | | 180=60+60+x-20 | | X(x+2)=71 | | 5x+4=31-2x | | 10x+5(0)=10 | | (7y+8)-(6+6y)=10 | | -1y=0 | | 2a+5(a+4)(a+1)+9(a+4)(a+3)(a+1)= | | 6x+20-x=-4x+2 | | -1=0 | | 3z+2=A | | 0.03(2c-26)=-0.6(c-2) | | 7d+3=31 | | 32+15n=-20n-73 | | 6m+3=17 | | 3x+14=74+3x | | -1y=-2 | | 107=3x-4 | | 4x+1=80 | | 4x+8Y=692 | | -2x-36=6x+20 | | 5x^2*y^2-20xy= | | x^2-36=3x | | -1+5+-15+1+-2+5+1+-6= | | X+3x-6=90 | | 6x+2y=23.52 | | -8+15+-2+-15+-4+13+-17+11= | | 6k-3-2k=k-22 | | x*x-14x+33=0 | | -5=-2-3 | | -6z=3x | | x=-7+7 |

Equations solver categories